Cloning of Guinea Pig Tissue Factor cDNA: Comparison of Primary Structure among Six Mammalian Species - Shi, Rui-Jin; Li, Wen-Zhou; Marder, Victor J.; Sporn, Lee Ann (Thrombosis and Haemostasis, 2000)
Tissue factor (TF) is a transmembrane glycoprotein that serves as an essential cofactor for plasma coagulation factor VII. TF procoagulant activity exhibits varying species specificity. In particular, guinea pig (GP) TF is unable to activate clotting in heterologous plasma systems, but the molecular basis for this phenomenon is not yet understood. The full-length GP TF cDNA was cloned and sequenced. The open reading frame encoded a predicted precursor protein of 289 amino acids (aa) which was expressed in a reticulocyte lysate system as a protein of apparent molecular weight of 34 kD. The identity of the predicted aa sequence of mature GP TF with rabbit, human, bovine, rat and mouse TF was 66.4, 64.4, 60.6, 53.2 and 52.2%, respectively. With a focus on sites of potential functional significance, we compared sequences within the known binding regions. The eleven residues at the interface region between the TF1 and TF2 modules, which bind to the EGF domain of VIIa, were perfectly conserved among the six species, with the exception of an isoleucine replacing a lysine in the guinea pig sequence. However, only four of the eleven binding residues in the TF1 module, known to interact with the catalytic domain of factor VII, and three of the five residues in the TF2 module, involved in binding the factor VII Gla domain, were conserved among species. We hypothesize that divergence at these regions contributes to the specificity and non-reciprocity of TF procoagulant activity between species.
Keywords: Tissue factor; guinea pig